Amonização do feno de Brachiaria decumbens com diferentes teores de umidade - Reis, R. A.; Rodrigues, LRA; Nahas, E.; BONJARDIM, SR; Pereira, JRA (Empresa Brasileira de Pesquisa Agropecuária (EMBRAPA), 1993)
The experiment was carried out to evaluate the effects of two moisture levels (18-20% and 13-15%) and three anhydrous ammonia levels (0.0; 1.5; 3.0% of NH3) on the quality of Brachiaria decumbens Stapf hay. The hay was bailed in April and weighed and treated under plastic cover during 30 days. The hay presented a similar chemical composition when bailed with high or low moisture. The percentages of NDF (80.59; 77.61; 76.10%); hemicellulose (32.56; 29.48; 28.76%) and lignin (9.53; 8.21; 7.54% decreased and the percentages of crude protein (4.04; 11.35; 13.22%) and IVDMD (36.78; 49.72; 54.33%) increased as the NH3 level increased. The fractions ADF, cellulose, and ADIN did not change due to the ammoniation. The incidence of fungi decreased with application of NH3 being the better results obtained with the 1.5% treatments.

O estudo foi conduzido na Universidade do Estado de São Paulo (UNESP), em Jaboticabal, SP, para avaliar os efeitos da aplicação de amônia anidra (0,0; 1,5 e 3,0% de NH3 na MS) e dos teores de umidade (18-20% e 13-15%) sobre a qualidade do feno do capim-braquiária (Brachiaria decumbens Stapf). A forragem, enfardada em abril, foi pesada, empilhada e tratada com NH3 sob lona plástica por 30 dias. Os fenos apresentaram composição química semelhante, quando enfardados com diferentes teores de umidade. A amonização diminuiu os teores de FDN (80,59; 77,61; 76,10%), de hemicelulose (32,56; 29,48; 28,76%) e de lignina (9,53; 8,21; 7,54%) e aumentou os teores de PB (4,04; 11,35; 13,22%) e a DIVMS (36,78; 49,72; 54,33%), respectivamente com a aplicação de 0,0; 1,5 e 3,0% de NH3. Não houve efeito da amonização sobre os teores de FDA, de celulose e de N insolúvel em detergente ácido. A incidência de fungos diminuiu com a amonização, principalmente com a aplicação de 1,5% de NH3.
Effect of ammoniation and moisture-content on the quality of signal grass (Brachiaria-decumbens stapf) hay
Keywords: ANHYDROUS AMMONIA; FORAGE GRASSES; MOISTURE LEVELS; TROPICAL GRASSES; CHEMICAL COMPOSITION; FUNGI DEVELOPMENT